The Relationship Between Gender, Age, and Medical History with Body Balance Disorders in the Examination Participants at MAN 2 Sleman, DIYw - Utami, Jacoba Nugrahaningtyas Wahjuning; Nurtyas, Maratusholikhah; Wulandari, Sri; Andriani, Githa (International Journal of Natural and Health Sciences, 2024)
Each responder has experienced balance disturbances. Frequent loss of balance can be a sign of an underlying health condition. The purpose of the study was to determine the relationship between gender, age, Medical History and anemia with balance disorders. The research method uses secondary data when doing community service at MAN 2 Sleman in May 2024. The results of female gender are more than male gender, namely 69.9% (58) respondents. The age of the majority of respondents is less than 25 years old, namely 68.7% (57) respondents.  A total of 48 respondents or (57.8%) who did not have a Medical History.   Respondents who did not experience anemia were 81.9% (68) of respondents.  Respondents who experienced balance disorders were less than those who were normal, namely those who experienced balance disorders of 62.7% (52) respondents.  Bivariate analysis found that the results of gender analysis using chi-square showed a p-value of more than 0.05, namely 0.744. Age 60 and over as many as 1 respondent experienced body balance disorders, age 25-59 who experienced body balance disorders as many as 16 respondents and age less than 25 years as many as 14 respondents who experienced body balance disorders and chi-square analysis showed a p-value of less than 0.05, namely 0.001, for a history of illness as many as 13 people who also experienced body balance disorders and analysis using chi-square showed that the p-value was more than 0.05 or 0.973. A total of 31 respondents out of 83 respondents who were anemic experienced balance disorders and chi-square analysis showed that the p-value was more than 0.05 or 0.126. Conclusion There is no association between gender, Medical History, and anemia with impaired body balance, there is an association between age and impaired body balance